Genetics of sporadic amyotrophic lateral sclerosis. - Schymick, J; Talbot, K; Traynor, B (2007)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized clinically by rapidly progressive paralysis leading ultimately to death from respiratory failure. There is substantial evidence suggesting that ALS is a heritable disease, and a number of genes have been identified as being causative in familial ALS. In contrast, the genetics of the much commoner sporadic form of the disease is poorly understood and no single gene has been definitively shown to increase the risk of developing ALS. In this review, we discuss the genetic evidence for each candidate gene that has been putatively associated with increased risk of sporadic ALS. We also review whole genome association studies of ALS and discuss the potential of this methodology for identifying genes relevant to motor neuron degeneration.